The long non‐coding RNAs MHRT, FENDRR and CARMEN, their expression levels in peripheral blood mononuclear cells in patients with essential hypertension and their relation to heart hypertrophy. (24th October 2018) - Kontaraki, Joanna E.; Marketou, Maria E.; Kochiadakis, George E.; Maragkoudakis, Spyros; Konstantinou, John; Vardas, Panos E.; Parthenakis, Fragiskos I.
Summary: Long non‐coding RNAs (lncRNAs) participate in the modulation of cardiac hypertrophy, and they represent potential therapeutic targets in cardiovascular disease. We investigated the expression profiles of selected lncRNAs in peripheral blood mononuclear cells of patients with essential hypertension in relation to left ventricular hypertrophy. We assessed the expression levels of the lncRNAs MHRT, FENDRR and CARMEN using real‐time reverse transcription polymerase chain reaction. Hypertensive patients showed significantly higher MHRT, FENDRR and CARMEN expression levels compared with healthy controls. In addition, we observed significant negative correlations of MHRT ( r = −0.323, P = 0.003) and FENDRR ( r = −0.380, P = 0.001) and a positive correlation of CARMEN ( r = 0.458, P < 0.001) expression levels with left ventricular mass index. Our data reveal that the lncRNAs MHRT, FENDRR and CARMEN show distinct expression profiles in hypertensive patients and they possibly represent candidate therapeutic targets in hypertensive heart disease.